Plasma wave resonant detection of terahertz radiations by nanometric transistors: Новые электронные материалы и системы - Knap, W.; Fatimy, A. El; Torres*, J.; Teppe, F.; Orlov, M.; Gavrilenko, V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
We report on resonant terahertz detection by two-dimensional electron plasma located innanometric InGaAs and GaN transistors. Up to now, the biggest part of the research was devotedto GaAs-based devices as the most promising from the point of view of the electron mobility. The resonant detection was reported, however, only in the sub-THz range. According to predictions of the Dyakonov–Shur plasma wave detection theory an increase of the detection frequency can be achieved by reducing the length or increase the carrier density in the gated region.We demonstrate that the 1THz limit can be overcome by using ultimately short gate InGaAs and GaN nanotransistors. For the first time the tunability of the resonant signal by the applied gate voltage is demonstrated. We show that the physical mechanism of the detection is related to the plasma waves excited in the transistor channel (Dyakonov–Shur theory). We also show that by increasing of the drain-to-source current leads to a transformation of the broadband detection to a resonant and tuneable one. We can get resonant detection at room temperature. We finally discuss the possible application of detection by nanotransistors in different types of THz spectroscopy research.